Flujo documental entre áreas administrativas de una entidad bancaria: Una aproximación desde el análisis de redes sociales (ARS) - Mogollón, Juan Bernardo Montoya [UNESP]; De Carvalho Madio, Telma Campanha [UNESP] (University Library System, University of Pittsburgh, 2016)
This paper analyses twelve administrative departments in a bank and their relationships in documentaries terms (flows). The study was developed by a research unit applying Social Network Analysis (SNA). The objetive of this research was identify the relationship ways between these areas, highlighting their strengths and/or weaknesses, and their relations with others areas in the organization. Finally, this analysis tries to offer the opportunity to understand how actors relate within an organization, to project possible solutions in terms of relationships and documentary dissemination, an activity with visible difficulties still today.
Documentary flow between administrative areas of a bank: An approach from the analysis of networks (SNA)
Keywords: Betweenness centrality; Closeness centrality; Companies; Degree centrality; Information dissemination; Records management; Social capital; Social network analyses